2000
DOI: 10.1037/0735-7036.114.4.325
|View full text |Cite
|
Sign up to set email alerts
|

Attractivity and social preferences in mice (Mus musculus domesticus): The role of prepubertal sexual segregation and of precocious weaning.

Abstract: Mice (Mus musculus domesticus) were raised (Postnatal Day 15 to 25) in single- or mixed-sex litters and precociously (Day 15) or regularly (Day 25) weaned. When they were faced as adults with a basic social choice--between two stimulus mice raised in litters of different sex composition but both of the same sex as the chooser--mice raised in mixed-sex litters were preferred. In the sociosexual choice-between a male and a female, both from the single- or the mixed-sex group--the opposite-sex preference was expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…V1bR+/+ mice prefer cues from female mice over male mice, a result consistent with previous reports (Mossman and Drickamer, 1996;Terranova et al, 2000;Wersinger and Rissman, 2000). Likewise, the V1bR+/+ mice are motivated to investigate social cues (either male-or female-soiled bedding) over bedding with no social cues.…”
Section: Discussionsupporting
confidence: 89%
“…V1bR+/+ mice prefer cues from female mice over male mice, a result consistent with previous reports (Mossman and Drickamer, 1996;Terranova et al, 2000;Wersinger and Rissman, 2000). Likewise, the V1bR+/+ mice are motivated to investigate social cues (either male-or female-soiled bedding) over bedding with no social cues.…”
Section: Discussionsupporting
confidence: 89%
“…In particular, drug-conditioned effects were significantly more marked in Wean-15 mice, when compared with the other two weaning groups. Consistently, previous reports associated early weaning with an increased sensitivity to cocaine's rewarding properties (Laviola and Dell'Omo 1997) and a higher responsivity to the modulatory effect of a delta-opioid agonist (Terranova and Laviola 2001), along with a numberof other neurobehavioral effects (Terranova and Laviola 1995;Loggi et al 1996;Terranova et al 2000). It seems important to note that manipulation of weaning time did not produce any leftward or rightward shift in the dose-response curve.…”
Section: Amph-induced Place Conditioningsupporting
confidence: 63%
“…Accordingly, when compared with a regular weaning group, animals weaned precociously show a number of behavioral (Martin and Bateson 1985;Terranova and Laviola 1995;Loggi et al 1996;Terranova et al 2000) and neurochemical (see e.g. Sharman et al 1982;Mann and Sharman 1983) changes, which can be regarded as signs of advanced ontogeny.…”
mentioning
confidence: 99%
“…In addition to such nutritional conditions, also the social environment an individual experiences during early development can affect the expression of phenotypic traits (Stamps & Groothuis, 2010). Yet, so far, most studies on the influence of social conditions during early development on subsequent behavioral traits have been conducted on small mammals (Laviola & Alleva, 1995;Laviola & Terranova, 1998;Mendl, 1988aMendl, , 1988bTerranova, Loggi, Chiarotti, & Laviola, 2000). Studies on mice showed, for instance, that litter size and sex ratio affect subsequent social behavior (Laviola & Terranova, 1998) and studies on guinea pigs (Cavia porcellus) showed that offspring from mothers experiencing a socially unstable environment during pregnancy were more aggressive than offspring from mothers that were in a stable social environment during pregnancy (Kaiser & Sachser, 2005).…”
Section: Introductionmentioning
confidence: 98%